Rethinking modernity and national identity in Turkey - Bozdoğan, Sibel; Kasaba, Reşat, 1954- (University of Washington Press, 1997)
The essays in this book are the first attempt to examine the Turkish experiment with modernity from a broad, interdisciplinary perspective, encompassing the fields of history, the social sciences, the humanities, architecture, and urban planning. The contributors offer a fresh, balanced understanding of dilemmas now facing not only Turkey but also many other parts of the Middle East and the world at large.
Keywords: Turkey -- Civilization -- 20th century.; Social change -- Turkey.; Nationalism -- Turkey.; East and West.; HISTORY / Middle East / General; Civilization; East and West; Nationalism; Social change; Turkey; Moderniteit.; Nationale identiteit.; Sociale verandering.; Cultuurverandering.; Turkije.; 1900-1999